Reproductive pattern of the large fruit-eating bat, Artibeus amplus (Chiroptera: Phyllostomidae) in the Venezuelan Andes - Ruiz-Ramoni, Damián; Ramoni-Perazzi, Paolo; Munoz-Romo, Mariana (Revista de Biología Tropical, 2017)
Bimodal polyestry is the most common reproductive pattern in tropical bats, and it consists in producing one offspring per female twice a year. Reproductive patterns are closely related to rainfall regimes, frequently occurring twice a year in tropical regions. The goal of our study was to determine the reproductive pattern of the large fruit-eating bat, Artibeus amplus Handley, 1987 in a cave in the Venezuelan Andes inhabited by a large, stable colony. Thus, in this study we describe for the first time this important biological aspect of this unknown Neotropical bat species through the examination of external reproductive characteristics of males (inguinal or scrotal testes) and females (pregnant, lactating, post-lactating), based on 211 individuals (120 males and 91 females) captured between September 2008 and August 2009, in Cueva del Parque Las Escaleras, Estado Táchira, Venezuela. During this period of monthly sampling for a full year, most males displayed large scrotal testes, averaging 10 mm maximum length. The examination of females indicated that although pregnancy was first observed in November 2008, it reached a maximum during January and February 2009. Although adult males with scrotal testes throughout the year could imply that females have more than one pregnancy, our results suggested a seasonally monoestrous reproductive pattern for A. amplus. This study represents the first report of reproductive pattern for this poorly-known Neotropical frugivorous species. The observed monoestrous reproductive pattern supports the existence of synchronization between precipitation and reproduction. This synchronization has been frequently observed in most species of fruit bats. In this study, Artibeus amplus presumably adjust the parturition to anticipate the rainy season, as a strategy that allows maintenance of offspring during high availability of fruits.